Gaya Bahasa Perulangan Pada Lirik Lagu Yura Yunita Dalam Album Tutur Batin dan Kepopuleran Lagunya: Kajian Stilistika - Febrian Shafa Harahap; Nurhayati Harahap; Emma Maersella (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to discuss the repetition of language style and the popularity of the song in the lyrics of Yura Yunita's song in the Tutur Batin Album. The theory applied in this study is the theory of stylistics. Language style plays an important role in assessing the beauty of a literary work. Tarigan states that there are four types of language style, namely, oppositional language style, comparative language style, linking language style, and repetition of language style. This study aims to describe the repetition of language style and the popularity of the song contained in the Tutur Batin album by Yura Yunita. The research method used is a qualitative descriptive method with data collection techniques using the listening and recording technique. The data in this study are the lyrics of the song in the Tutur Batin album. From the results of the study, seven types of repetition of language style were found, namely: (1) alliteration, (2) assonance, (3) anaphora, (4) mesodilopsis, (5) epizeukis, (6) antanaklasis and (7) simploke. Furthermore, the popularity of the songs in this album was found from the influence of the repetitive language style originating from the questionnaire answers of Indonesian Literature students at the University of North Sumatra. The popularity comes from the use of repetitive language style in the song lyrics, which makes the songs of the Tutur Batin album easier to remember by music listeners. From the results of the study using Likert scale calculations, 80.34% of Indonesian Literature students at the University of North Sumatra filled out a questionnaire that the repetitive language style influenced the popularity of the songs of the Tutur Batin album.